2010
DOI: 10.1002/emmm.201000105
|View full text |Cite
|
Sign up to set email alerts
|

Hsp72 is an early and sensitive biomarker to detect acute kidney injury

Abstract: This study was designed to assess whether heat shock protein Hsp72 is an early and sensitive biomarker of acute kidney injury (AKI) as well as to monitor a renoprotective strategy. Seventy-two Wistar rats were divided into six groups: sham-operated and rats subjected to 10, 20, 30, 45 and 60 min of bilateral ischemia (I) and 24 h of reperfusion (R). Different times of reperfusion (3, 6, 9, 12, 18, 24, 48, 72, 96 and 120 h) were also evaluated in 30 other rats subjected to 30 min of ischemia. Hsp72 messenger RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 48 publications
(74 reference statements)
4
50
2
3
Order By: Relevance
“…Furthermore, HSP72 has been reported as an early and sensitive urinary biomarker of acute kidney injury in several studies . To our knowledge, this is the first study evaluating uHSP72 levels in DN in T2DM patients, in which uHSP72 levels were significantly increased in both micro‐ and macroalbuminuric diabetics compared with normoalbuminuric diabetics and healthy controls, indicating its positive association with disease progression.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, HSP72 has been reported as an early and sensitive urinary biomarker of acute kidney injury in several studies . To our knowledge, this is the first study evaluating uHSP72 levels in DN in T2DM patients, in which uHSP72 levels were significantly increased in both micro‐ and macroalbuminuric diabetics compared with normoalbuminuric diabetics and healthy controls, indicating its positive association with disease progression.…”
Section: Discussionmentioning
confidence: 68%
“…All procedures were performed according to the manufacturer's instructions. Because we recently showed that heat-shock protein 72 (Hsp72) is a sensitive biomarker of AKI [31], urinary Hsp72 levels were analyzed by using a commercially available high-sensitivity ELISA (ADI-EKS-715; Assay Designs, Ann Arbor, Mich., USA). Briefly, samples and standards were added to wells coated with a mouse monoclonal antibody.…”
Section: Methodsmentioning
confidence: 99%
“…21,22 Similarly, HSP70 may indicate early diabetic kidney injury because it has been shown in experimental models of acute kidney injury and gentamicin-induced renal tubular injury in Human Kidney tubular cell line (HK-2) that uHSP70 is a useful marker for early detection of proximal tubular cell injury. 23,24 DN is a consequence of exposure to consistent high plasma glucose concentration and various other metabolic factors such as advanced glycosylated end products (AGEs), oxidative stress, growth factors, and cytokines.…”
Section: Discussionmentioning
confidence: 99%